Corrosion-resistant materials

By forming a combined structure of buffer layer and corrosion-resistant coating on the metal substrate, the problem of coating peeling under the action of thermal history of existing corrosion-resistant members is solved, and higher corrosion resistance and thermal stability are achieved.

JP7661885B2Active Publication Date: 2025-04-15RESONAC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021550484
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-07
Filing Date
2020-09-03
Publication Date
2025-04-15
Estimated Expiration
2040-09-03

AI Technical Summary

Technical Problem

The existing corrosion-resistant members are subject to thermal history and the corrosion-resistant coating is easily peeled off, resulting in reduced performance and particle generation.

Method used

A metal substrate containing main elements and trace elements is used, and a buffer layer is formed in the middle. The buffer layer consists of the same trace elements, with a content ranging from 2% to 99%, and a corrosion-resistant coating composed of magnesium fluoride, aluminum fluoride or aluminum oxide is formed on the substrate.

Benefits of technology

Effectively prevent corrosion-resistant coating from peeling off under the action of thermal history, improve corrosion resistance, reduce particle generation, and enhance corrosion resistance to highly corrosive gases and plasmas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661885000002
    Figure 0007661885000002
  • Figure 0007661885000003
    Figure 0007661885000003
  • Figure 0007661885000001
    Figure 0007661885000001
Patent Text Reader

Abstract

Provided is a corrosion-resistant member in which a corrosion-resistant film does not readily separate from a substrate even after having received a thermal history. The corrosion-resistant member comprises a metal substrate (10), a corrosion-resistant film (30) formed on the surface of the substrate (10), and a buffer layer (20) formed between the substrate (10) and the corrosion-resistant film (30). The substrate (10) contains a main element, which is an element for which the mass content is highest among the elements contained in the substrate (10), and a trace element, which is an element for which the mass content is equal to or less than 1 mass%. The corrosion-resistant film (30) is configured from at least one selected from magnesium fluoride, aluminum fluoride, and aluminum oxide. The buffer layer (20) contains an element that is the same as the trace element. The element content for the element contained in the buffer layer (20) that is the same as the trace element is 2-99 mass% (inclusive), according to energy-dispersive X-ray analysis.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a corrosion-resistant member. [Background technology]

[0002] In semiconductor manufacturing processes, highly corrosive gases such as chlorine gas and fluorine gas may be used, and therefore corrosion resistance is required for components constituting semiconductor manufacturing equipment. Examples of components constituting semiconductor manufacturing equipment include chambers, piping, gas storage devices, valves, susceptors, shower heads, etc. Patent Document 1 discloses a corrosion-resistant member in which a corrosion-resistant coating made of a magnesium fluoride film is formed on the surface of a metal substrate. Patent Document 2 discloses a corrosion-resistant aluminum alloy material in which the surface of a substrate made of an aluminum alloy containing magnesium is covered with a corrosion-resistant coating made of a fluoride passivation film containing magnesium fluoride. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2000-169953 [Patent Document 2] Japanese Patent Publication No. 66657, 1992 Summary of the Invention [Problem to be solved by the invention]

[0004] However, the corrosion-resistant members disclosed in Patent Documents 1 and 2 have a problem in that the corrosion-resistant coating is easily peeled off from the substrate due to thermal history. An object of the present invention is to provide a corrosion-resistant member having a corrosion-resistant coating that is not easily peeled off from a substrate even when subjected to a thermal history. [Means for solving the problem]

[0005] In order to solve the above problems, one aspect of the present invention is as follows [1] to [5]. [1] A metal substrate, a corrosion-resistant coating formed on a surface of the substrate, and a buffer layer formed between the substrate and the corrosion-resistant coating; The base material contains a major element that is an element having the highest mass content among the elements contained in the base material, and a trace element that is an element having a mass content of 1 mass% or less, the corrosion-resistant coating is composed of at least one material selected from magnesium fluoride, aluminum fluoride, and aluminum oxide; The buffer layer contains an element of the same type as the trace element, and the content of the element of the same type as the trace element contained in the buffer layer as determined by energy dispersive X-ray analysis is 2 mass% or more and 99 mass% or less.

[0006] [2] The corrosion-resistant member according to [1], wherein the main element is aluminum. [3] The corrosion-resistant member according to [1] or [2], wherein the trace element is at least one selected from the group consisting of chromium, nickel, iron, and copper.

[0007] [4] The corrosion-resistant member according to any one of [1] to [3], wherein the buffer layer has a thickness of 5 nm or more and 100 nm or less. [5] The corrosion-resistant member according to any one of [1] to [4], wherein the corrosion-resistant coating has a thickness of 100 nm or more and 50,000 nm or less. Effect of the Invention

[0008] In the corrosion-resistant member according to the present invention, the corrosion-resistant coating is unlikely to peel off from the substrate even when subjected to a thermal history. [Brief description of the drawings]

[0009] [Figure 1] 1 is a cross-sectional view illustrating a configuration of a corrosion-resistant member according to an embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view illustrating the configuration of a modified example of the corrosion-resistant member in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] An embodiment of the present invention will be described below. Note that this embodiment is merely an example of the present invention, and the present invention is not limited to this embodiment. In addition, various modifications and improvements can be made to this embodiment, and such modifications and improvements can also be included in the present invention.

[0011] 1, the corrosion-resistant member according to this embodiment includes a metal substrate 10, a corrosion-resistant coating 30 formed on the surface of the substrate 10, and a buffer layer 20 formed between the substrate 10 and the corrosion-resistant coating 30. That is, the buffer layer 20 is formed on the surface of the substrate 10, and the corrosion-resistant coating 30 is formed on the buffer layer 20.

[0012] The substrate 10 contains a main element that is the element with the highest mass content among the elements contained in the substrate 10, and trace elements (e.g., impurity elements, elements that form alloys) that are elements with a mass content of 1 mass% or less. Here, the mass content of the main element in the substrate 10 is preferably 50 mass% or more. The corrosion-resistant coating 30 is made of at least one material selected from magnesium fluoride (MgF2), aluminum fluoride (AlF3), and aluminum oxide (Al2O3).

[0013] The buffer layer 20 contains the same elements as the above-mentioned trace elements. The content of the elements similar to the trace elements contained in the buffer layer 20 by energy dispersive X-ray analysis (EDS analysis) is 2% by mass or more and 99% by mass or less. That is, the buffer layer 20 is a layer constituted by the same type of element as the trace element contained in the base material 10, or a layer containing the same type of element as the trace element contained in the base material 10 and having a high concentration of the same type of element. The buffer layer 20 may contain the same type of element as the trace element as at least one of a metal, an intermetallic compound, an alloy, an oxide, and a fluoride.

[0014] The corrosion-resistant member according to the present embodiment has excellent corrosion resistance even in highly corrosive gases and plasmas because it has the corrosion-resistant coating 30. In addition, because it has the buffer layer 20, the corrosion-resistant coating 30 is unlikely to peel off from the substrate 10 even when subjected to thermal history. As a result, the corrosion-resistant member according to the present embodiment has excellent corrosion resistance even when subjected to thermal history, and the generation of particles resulting from the peeling of the corrosion-resistant coating 30 is suppressed. Furthermore, even if trace elements contained in the substrate 10 diffuse to the surface of the substrate 10, the trace elements are captured by the buffer layer 20, so that the generation of particles containing the trace elements from the corrosion-resistant member is suppressed.

[0015] The corrosion-resistant member according to this embodiment is suitable as a member that requires corrosion resistance and heat resistance, for example, as a member constituting a semiconductor manufacturing apparatus (particularly, a film-forming apparatus using a chemical vapor deposition method). As a specific example, it is suitable as a susceptor or shower head of a film-forming apparatus that forms a thin film on a wafer. If the corrosion-resistant member according to this embodiment is used as a member constituting a semiconductor manufacturing apparatus, the generation of particles is suppressed, and semiconductors can be manufactured with a high yield.

[0016] The corrosion-resistant member of this embodiment can be manufactured, for example, by forming a layer consisting of the same type of element as the trace element or a layer containing the same type of element as the trace element (buffer layer 20) on the surface of the substrate 10 by a method such as sputtering, and then forming a corrosion-resistant coating 30 on the buffer layer 20 by a method such as electrophoretic deposition or vapor deposition.

[0017] The metal constituting the substrate 10 may be a single metal (containing unavoidable impurities) or an alloy. The main element, which is the element with the highest mass content among the elements contained in the substrate 10, is preferably aluminum, and the trace element is preferably at least one selected from chromium, nickel, iron, copper, silicon, titanium, and manganese. An example of an element contained in the substrate 10 other than the main element and the trace element is magnesium.

[0018] Furthermore, the thickness of the buffer layer 20 is preferably 5 nm or more and 100 nm or less. Furthermore, the thickness of the corrosion-resistant coating 30 is preferably 100 nm or more and 50,000 nm or less. If the thickness of the buffer layer 20 is 5 nm or more and 100 nm or less, the effect that the corrosion-resistant coating 30 is less likely to peel off from the substrate 10 even when subjected to thermal history is enhanced. If the thickness of the corrosion-resistant coating 30 is 100 nm or more and 50,000 nm or less, the corrosion resistance is more excellent. The method for measuring the thickness of the buffer layer 20 and the corrosion-resistant coating 30 is not particularly limited, but examples thereof include a transmission electron microscope (TEM), a scanning transmission electron microscope (STEM), a scanning electron microscope (SEM), and the like.

[0019] Magnesium fluoride, a corrosion-resistant coating, is made up of magnesium fluoride (MgF2), magnesium fluoride hydrate (MgF2·nH2O), and magnesium fluoride containing some hydroxyl groups (MgF 2-X (OH) X ), magnesium fluoride hydrate containing some hydroxyl groups (MgF 2-X (OH) X nH2O), magnesium fluoride containing some oxygen (MgF 2 (1-X) O X ), and partially oxygenated magnesium fluoride hydrate (MgF 2 (1-X) O X At least one selected from the group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64

[0020] Similarly, aluminum fluoride can be classified as aluminum fluoride (AlF3), aluminum fluoride hydrate (AlF3·nH2O), or partially hydroxylated aluminum fluoride (AlF 3-X (OH) X ), aluminum fluoride hydrate containing some hydroxyl groups (AlF 3-X (OH) X nH2O), aluminum fluoride containing some oxygen (AlF 3 (1-X) O 3 / 2X ), and partially oxygenated aluminum fluoride hydrate (AlF 3 (1-X) O 3 / 2X At least one selected from the group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32

[0021] Similarly, aluminum oxide can be classified as aluminum oxide (Al2O3), aluminum oxide hydrate (Al2O3·nH2O), or aluminum oxide containing some hydroxyl groups (Al2O 3-X (OH) 2X ), aluminum oxide hydrate (AlO 3-X (OH) 2X nH2O), aluminum oxide containing some fluorine (Al2O 3-X F 2X ), and partially fluorinated aluminum oxide hydrate (AlO 3-X F 2X At least one selected from the group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32

[0022] In addition, the corrosion-resistant member may have a corrosion-resistant coating 30 composed of multiple layers (two layers 31 and 32 in the example of FIG. 2) as in the modified example shown in FIG. 2. These multiple layers are composed of different types of compounds. For example, in the case where the corrosion-resistant coating 30 is composed of two layers 31 and 32 as in the example of FIG. 2, the layer 31 may be composed of magnesium fluoride and the layer 32 may be composed of aluminum fluoride. EXAMPLES

[0023] The present invention will be described more specifically below with reference to examples and comparative examples. Example 1 A buffer layer was formed on the surface of the substrate by sputtering, and then a corrosion-resistant coating was formed on the buffer layer by electrophoretic deposition. The corrosion-resistant coating was then subjected to post-treatment to obtain a corrosion-resistant member.

[0024] The metal constituting the substrate is aluminum alloy A5052 containing 2.55 mass% magnesium, and the following trace elements: 0.23 mass% chromium, 0.04 mass% nickel, 0.26 mass% iron, and 0.07 mass% copper.

[0025] First, the substrate was pretreated. The substrate was immersed in a degreasing solution at 50°C, which was prepared by dissolving 70g of S-clean AL-13 (manufactured by Sasaki Chemical Co., Ltd.) in 1L of water, for 10 minutes, and then washed with pure water. Next, the substrate washed as described above was immersed in an etching solution of 500g of S-clean AL-5000 (manufactured by Sasaki Chemical Co., Ltd.) heated to 70°C for 1 minute, and then washed with pure water. After that, the substrate was immersed in a smut removal solution at 25°C, which was prepared by dissolving 200g of Smut Clean (manufactured by Raiki Co., Ltd.) in 400g of water, for 30 seconds, washed with pure water, and dried in vacuum to complete the pretreatment of the substrate.

[0026] Next, sputtering was performed on the above pretreated substrate in order to form a buffer layer. The metals constituting the buffer layer are the same elements as the trace elements, and are chromium, nickel, iron, and copper. An alloy containing chromium, nickel, iron, and copper was prepared as a target, and the target was placed on the cathode of a DC magnetron sputtering device. The pretreated substrate was placed opposite the target, and the distance between the target and the pretreated substrate was set to 50 mm. 1×10 -3 After evacuation to a pressure of 10 Pa or less, argon gas was introduced to set the pressure to 10 Pa, and DC power was applied to the target for treatment for 30 seconds. The DC discharge power was 50 W.

[0027] Next, a corrosion-resistant coating was formed by electrophoretic deposition. The compound constituting the corrosion-resistant coating was magnesium fluoride. The conditions of the electrophoretic deposition method were as follows. First, 5 g of MgF2 powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) with a purity of 99.99% or more was dispersed in 495 g of ethanol to which 0.15 g of S-ream (registered trademark) C-2093I (manufactured by NOF Corporation) was added as a dispersing agent, and a bead mill treatment was performed to prepare an MgF2 suspension having a primary particle size of 30 nm. In this suspension, a negative electrode having dimensions of 20 mm x 25 mm x 2 mm made of the above-mentioned sputtered base material and a positive electrode made of carbon were immersed with an electrode distance of 30 mm, and a constant voltage of 50 V was applied for 120 seconds to form a particle film made of MgF2 with a thickness of about 2 μm on the surface of the negative electrode. The post-treatment method for the corrosion-resistant coating is a heat treatment in an atmosphere containing fluorine gas (F2). The post-treatment conditions are: fluorine gas concentration in the atmosphere is 1% by volume, nitrogen gas concentration is 99% by volume, the heat treatment temperature is 350°C, and the heat treatment time is 900 min.

[0028] The obtained corrosion-resistant components were subjected to a heating test to evaluate the state of peeling of the corrosion-resistant coating. The heating test conditions were as follows: in a nitrogen gas atmosphere, the temperature was raised from room temperature to 300°C over three hours, and then the temperature was held at 300°C for five hours, followed by natural cooling to room temperature. This process was considered as one cycle, and this cycle was repeated 10 times.

[0029] After the heating test was completed, the corrosion-resistant coating of the corrosion-resistant component was observed with a scanning electron microscope to evaluate the degree of peeling. The results are shown in Table 1. In Table 1, if the area of ​​the peeled part of the corrosion-resistant coating was less than 1% of the area of ​​the corrosion-resistant coating, it is indicated as A, if it was 1% or more but less than 10%, it is indicated as B, if it was 10% or more but less than 30%, it is indicated as C, and if it was 30% or more, it is indicated as D.

[0030] In addition, the amount of elements (same kind of elements as trace elements) present on the surface of the corrosion-resistant coating was measured by inductively coupled plasma mass spectrometry (ICP-MS) before and after the heating test. First, the corrosion-resistant member before the heating test was immersed in 100 mL of nitric acid with a concentration of 0.3 mass% for 5 minutes to extract the elements present on the surface of the corrosion-resistant coating, and a solution was obtained. The obtained solution was analyzed by ICP-MS to measure the amount of elements before the heating test. The same operation was performed on the corrosion-resistant member after the heating test, and the amount of elements after the heating test was measured.

[0031] The increase rate (%) of each element before and after the heating test was calculated using the following formula. (Increase in element before and after heating test) = 100 × {(element amount after heating test) - (element amount before heating test)} / (element amount before heating test) The results are shown in Table 1. In Table 1, when the "increase rate of an element before and after the heating test" calculated by the above formula was less than 200%, it is indicated as A, when it was 200% or more and less than 500%, it is indicated as B, when it was 500% or more and less than 1000%, it is indicated as C, and when it was 1000% or more, it is indicated as D.

[0032] [Table 1]

[0033] Example 2 A corrosion-resistant member was manufactured and evaluated in the same manner as in Example 1, except that the metal constituting the substrate was aluminum alloy A6061 containing 0.84 mass% magnesium and 0.78 mass% silicon. The results are shown in Table 1. The aluminum alloy A6061 contains 0.16 mass% chromium, 0.04 mass% nickel, 0.52 mass% iron, and 0.25 mass% copper as trace elements.

[0034] Example 3 A corrosion-resistant member was manufactured and evaluated in the same manner as in Example 1, except that the concentration of nitrogen gas in the post-treatment conditions was 100% by volume, the heat treatment temperature was 450°C, and the compound constituting the corrosion-resistant coating was aluminum oxide. The corrosion-resistant coating was formed by electrophoretic deposition in the same manner as in Example 1, and a particle film was formed using 5 g of aluminum oxide hydroxide (manufactured by FUJIFILM Wako Chemical Co., Ltd.). The primary particle size after the bead mill treatment was 21 nm. The aluminum oxide hydroxide was heat-treated at 450°C to become a sintered aluminum oxide film. The results are shown in Table 1.

[0035] Example 4 A corrosion-resistant member was manufactured and evaluated in the same manner as in Example 1, except that the compound constituting the corrosion-resistant coating was aluminum fluoride. The corrosion-resistant coating was formed by electrophoretic deposition, as in Example 1, and a particle film was formed using 5 g of aluminum fluoride powder (manufactured by FUJIFILM Wako Chemical Co., Ltd.). The primary particle size after bead mill processing was 27 nm. The results are shown in Table 1.

[0036] Example 5 A corrosion-resistant member was manufactured and evaluated in the same manner as in Example 1, except that the compounds constituting the corrosion-resistant coating were magnesium fluoride and aluminum fluoride. The results are shown in Table 1. In Example 5, the corrosion-resistant coating is composed of two layers, a layer made of magnesium fluoride and a layer made of aluminum fluoride, as in the modified example shown in FIG. 2. The corrosion-resistant coating was formed by electrophoretic deposition, as in Example 1, and a particle film was formed using 5 g of magnesium fluoride powder (same as in Example 1) and 5 g of aluminum fluoride powder (same as in Example 4). The primary particle sizes after the bead mill treatment were 33 nm and 24 nm, respectively.

[0037] Example 6 A corrosion-resistant member was manufactured and evaluated in the same manner as in Example 1, except that the method for forming the corrosion-resistant coating was a vacuum deposition method. The results are shown in Table 1. The corrosion-resistant coating in Example 6 was formed as follows. First, the base material that had been subjected to sputtering was placed in a vacuum chamber, and then the pressure was increased to 2×10 -4 The vacuum chamber was evacuated until the pressure reached 10 Pa. The sputtered substrate was then heated to 380°C. A magnesium fluoride sintered material was used as the deposition material, and an electron beam was irradiated onto the sintered material. The shutter was opened, and a magnesium fluoride layer of 2.0 μm in thickness was formed on the sputtered substrate. The input power of the electron beam was about 40 mA at an acceleration voltage of 5 kV, and the degree of vacuum during vacuum deposition was 5×10 -4 The name was Pa.

[0038] Comparative Example 1 A corrosion-resistant member was produced and evaluated in the same manner as in Example 1, except that the corrosion-resistant coating was formed directly on the surface of the substrate without forming a buffer layer. The results are shown in Table 1. Comparative Example 2 A corrosion-resistant member was produced and evaluated in the same manner as in Example 2, except that the corrosion-resistant coating was formed directly on the surface of the substrate without forming a buffer layer. The results are shown in Table 1.

[0039] As can be seen from Table 1, almost no peeling of the corrosion-resistant coating occurred even after the thermal history was applied in Examples 1 to 6. Furthermore, even after the thermal history was applied, the trace elements contained in the substrate hardly diffused to the surface of the corrosion-resistant coating. [Explanation of symbols]

[0040] 10...Base material 20. Buffer layer 30. Corrosion-resistant coating

Claims

1. A metal substrate, a corrosion-resistant coating formed on a surface of the substrate, and a buffer layer formed between the substrate and the corrosion-resistant coating, The base material contains a main element that is an element having the highest mass content among the elements contained in the base material, and a trace element that is an element having a mass content of 1 mass% or less, The trace element is at least one selected from chromium, nickel, iron, and copper; the corrosion-resistant coating is composed of at least one material selected from magnesium fluoride, aluminum fluoride, and aluminum oxide; a buffer layer containing an element similar to the trace element, and a content of the element similar to the trace element contained in the buffer layer, as determined by energy dispersive X-ray analysis, of 2 mass % or more and 99 mass % or less.

2. 2. The corrosion resistant member according to claim 1, wherein said main element is aluminum.

3. 3. The corrosion-resistant member according to claim 1, wherein the buffer layer has a thickness of 5 nm or more and 100 nm or less.

4. The corrosion-resistant member according to any one of claims 1 to 3, wherein the corrosion-resistant coating has a thickness of 100 nm or more and 50,000 nm or less.

Citation Information

Patent Citations

  • Corrosion resistance aluminum article for semiconductor processing device

    JP1996181048A

  • Vacuum chamber member and its production

    JP1999061410A

  • Corrosion resistant member

    JP2000169953A

  • Aluminum alloy to be film-formed, aluminum alloy material superior in corrosion resistance and manufacturing method therefor

    JP2003119539A

  • JP466657B